African primary care research: Quality improvement cycles - Claire Van Deventer; Bob Mash (African Journal of Primary Health Care & Family Medicine, 2014)
Improving the quality of clinical care and translating evidence into clinical practice is commonly a focus of primary care research. This article is part of a series on primary care research and outlines an approach to performing a quality improvement cycle as part of a research assignment at a Masters level. The article aims to help researchers design their quality improvement cycle and write their research project proposal.